1990
DOI: 10.1128/aac.34.6.1214
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of 3'-fluoro-3'-deoxythymidine and 3'-deoxy-2',3'-didehydrothymidine in rhesus monkeys

Abstract: nucleoside analogs which inhibit human and simian immunodeficiency virus in vitro. The pharmacokinetic properties of these compounds in rhesus monkeys after intravenous, oral, and subcutaneous administration of the drug were compared. Half-lives, total clearances, and steady-state volumes of distribution for the two drugs were determined. The half-lives for the drugs by the different routes were between 0.58 and 1.4 h. Oral bioavailabllity of 3'-deoxy-2',3'-didehydrothymidine was incomplete, with an average of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
39
4

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 23 publications
8
39
4
Order By: Relevance
“…However, the rate of entry of [ 3 H]-AZT into the CSF, as determined by multiple-time point analysis, was 0.77+0.16 ml min 71 g 71 and was found not to be signi®cantly di erent than that obtained for [ 3 H]-D4T. This agrees with data from a clinical trial in children (Kline et al, 1995) and laboratory based studies in adult rhesus monkeys and adult and infant macaques (Schinazi et al, 1990;Keller et al, 1995), which have shown that D4T and AZT enter the CSF to a similar extent.…”
Section: Cerebrumsupporting
confidence: 80%
See 2 more Smart Citations
“…However, the rate of entry of [ 3 H]-AZT into the CSF, as determined by multiple-time point analysis, was 0.77+0.16 ml min 71 g 71 and was found not to be signi®cantly di erent than that obtained for [ 3 H]-D4T. This agrees with data from a clinical trial in children (Kline et al, 1995) and laboratory based studies in adult rhesus monkeys and adult and infant macaques (Schinazi et al, 1990;Keller et al, 1995), which have shown that D4T and AZT enter the CSF to a similar extent.…”
Section: Cerebrumsupporting
confidence: 80%
“…The octanol-saline partition coe cient determined for [ 3 H]-D4T was 0.167 and a similar value of 0.11 has previously been reported (Schinazi et al, 1990). The hydrophilic control, D-[ 14 C]-mannitol, mainly partitioned in the saline phase yielding a partition coe cient of 0.002.…”
Section: Cerebrumsupporting
confidence: 54%
See 1 more Smart Citation
“…In a study using monkeys and isolated rat hepatocytes, the degradation of stavudine was detected in thymine (12) and the d4T-TP derivative, with subsequent production of beta aminoisobutyric acid (BAI-BA) (13) (Cretton et al, 1993). The glucuronide metabolite (14) of stavudine was found in the urine of monkeys but has remained controversial (Schinazi, et al, 1990).A recent study reported by our group (Freitas, 2009) described the metabolic profile of stavudine, applying in vivo, in vitro and in silico approaches. The bioconversion experiments with nine strains of filamentous fungi, detected one major metabolite, which was further identified as thymine (12).…”
mentioning
confidence: 99%
“…Liver-derived HepG-2 and BC2 cell lines and lung-derived line A549 have the disadvantage of expressing few enzymes, restricting their metabolic capacity (Yoshitomi et al, 2001;Le Vee et al, 2006). However, the recent human hepatoma-derived cell line HepaRG has been shown to possess functions and morphological resemblance to normal human hepatocytes (Aninat et al, 2006).The use of microorganisms as models of mammalian metabolism was introduced in the early 1970s by Smith and Rosazza (Smith, Rosazza, 1974, 1975. This method uses eukaryotic microorganisms to produce metabolites similar to mammals, since microbial transformation systems could closely mimic most of the Phase I transformations of drugs observed in mammals, mainly those catalyzed by cytochrome P450 (Azerad, 1999).…”
mentioning
confidence: 99%